Total Intracorporeal Robot Kidney Autotransplantation: Case Report and Description of Surgical Technique - Van Praet, Charles; Lambert, Edward; Desender, Liesbeth; Van Parys, Benjamin; Vanpeteghem, Caroline; Decaestecker, Karel (Frontiers in Surgery, 2020)
Introduction and Objectives: Kidney autotransplantation can be performed in patients with complex renal or ureteral pathology not suitable for in situ reconstruction, such as renal vasculature anomalies, patients with proximal or long complex ureteral strictures, or complex oncological cases. Robot-assisted surgery allows for a high-quality vascular and ureteral anastomosis and faster patient recovery. Robot-assisted kidney autotransplantation (RAKAT) is performed in two phases: nephrectomy and pelvic transplantation. In-between, extraction of the kidney allows for vascular reconstruction or kidney modification on the bench and safe cold ischemia can be established. If no bench reconstruction is needed, total intracorporeal RAKAT (tiRAKAT) is feasible. One case report in Europe has been described; however, to our knowledge no surgical video is available. Methods: A 58 year-old woman suffered from right mid- and distal ureteral stenosis following pelvic radiotherapy 10 years prior for cervical cancer. A JJ stent was placed, but she suffered from recurrent urinary tract infections, and ultimately a nephrostomy was placed. Renogram demonstrated 43% relative right kidney function. As her bladder volume was low following radiotherapy, no Boari flap was possible and the patient refused life-long nephrostomy or nephrectomy. Therefore, tiRAKAT was performed using the DaVinci Xi system. Results: We describe our surgical technique including a video. Surgical time (skin-to-skin) was 5 h and 45 min. Warm ischemia time was 4 min, cold ischemia 55 min, and rewarming ischemia 15 min. The abdominal catheter and bladder catheter were removed on the first and second postoperative day, respectively. The JJ stent was removed after 4 weeks. The patient suffered from pulmonary embolism on the second postoperative day, for which therapeutic low molecular weight heparin was started. No further complications occurred during the first 90 postoperative days. After 7 months, overall kidney function remained stable, right kidney function dropped non-significantly from 27 to 25.2 mL/min (−6.7%) on renal scintigraphy. Conclusion: We demonstrated feasibility and, for the first time, a surgical video of tiRAKAT highlighting patient positioning, trocar placement, and intracorporeal cold ischemia technique.